(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyzes the murals Marion and Grace Greenwood created in the cities of Taxco and Morelia between 1933 and 1934. This article identifies elements relating to the Mexican muralist movement, the artists’ vision of Mexico, and the challenges the artists faced in Mexico, without neglecting other aspects that will allow a better understanding of their work, its cultural heritage, and the social and political context of their time.